Chemokine axes in breast cancer: factors of the tumor microenvironment reshape the CCR7‐driven metastatic spread of luminal‐A breast tumors. Issue 6 (2nd March 2016) - Weitzenfeld, Polina; Kossover, Olga; Körner, Cindy; Meshel, Tsipi; Wiemann, Stefan; Seliktar, Dror; Legler, Daniel F.; Ben‐Baruch, Adit
Abstract : Luminal‐A‐specific regulation of the CCR7‐CCL21 axis in cancer LN metastasis Abstract : Chemokine axes have been shown to mediate site‐specific metastasis in breast cancer, but their relevance to different subtypes has been hardly addressed. Here, with the focus on the CCR7‐CCL21 axis, patient datasets demonstrated that luminal‐A tumors express relatively low CCR7 levels compared with more aggressive disease subtypes. Furthermore, lymph node metastasis was not associated with high CCR7 levels in luminal‐A patients. The metastatic pattern of luminal‐A breast tumors may be influenced by the way luminal‐A tumor cells interpret signals provided by factors of the primary tumor microenvironment. Thus, CCR7‐expressing human luminal‐A cells were stimulated simultaneously by factors representing 3 tumor microenvironment arms typical of luminal‐A tumors, hormonal, inflammatory, and growth stimulating: estrogen + TNF‐α + epidermal growth factor. Such tumor microenvironment stimulation down‐regulated the migration of CCR7‐expressing tumor cells toward CCL21 and inhibited the formation of directional protrusions toward CCL21 in a novel 3‐dimensional hydrogel system. CCL21‐induced migration of CCR7‐expressing tumor cells depended on PI3K and MAPK activation; however, when CCR7‐expressing cancer cells were prestimulated by tumor microenvironment factors, CCL21 could not effectively activate these signaling pathways. In vivo, pre‐exposure of the tumor cells to tumor microenvironment factors has put restraints on CCL21‐mediated lymph node‐homing cues and shifted the metastatic pattern of CCR7‐expressing cells to the aggressive phenotype of dissemination to bones. Several of the aspects were also studied in the CXCR4‐CXCL12 system, demonstrating similar patient and in vitro findings. Thus, we provide novel evidence to subtype‐specific regulation of the CCR7‐CCL21 axis, with more general implications to chemokine‐dependent patterns of metastatic spread, revealing differential regulation in the luminal‐A subtype.